Anxiety relaxation during MRI with a patient-friendly audiovisual system. Issue 3 (August 2022) - Shimokawa, K.; Matsumoto, K.; Yokota, H.; Kobayashi, E.; Hirano, Y.; Masuda, Y.; Uno, T.
Abstract: Introduction: Many patients experience anxiety, not limited to claustrophobia, before magnetic resonance imaging (MRI) examination. We performed a non-randomized controlled trial to evaluate whether a patient-friendly audiovisual (AV) system in the MR scanner room reduces patient anxiety. Methods: We randomly selected 61 participants from outpatients who required brain MRI examination. Patients were informed that they could choose to undergo an MRI examination with a patient-friendly AV system (Ambient Experience, Philips Healthcare, Best, The Netherlands) or the standard system. To complete the MRI examination without affecting clinical practice, all patients who preferred the patient-friendly AV system were assigned to the preferring AV group. Patients who indicated that either system was acceptable were randomly assigned to the no preference but allocated AV group or control (using the standard system) groups. In both groups, state anxiety using the State-Trait Anxiety Inventory (STAI) was assessed before and after the MRI examination (A-State-before and A-State-after MRI, respectively). The changes in A-State-before and A-State-after MRI were categorized as follows: relieved high-state anxiety, no change in high-state anxiety, stable easiness, and intensified anxiety. Results: Among the 61 included patients, 19 were assigned to the preferring AV group, 20 to the no preference but allocated AV group, and 22 to the control group. There were no significant differences between the group. However, in patients with high-state anxiety before MRI, the preferring AV group and the no preference but allocated AV group, which used the patient-friendly AV system, relieved high-state anxiety by 63.6% (7 of 11 patients) and 81.8% (9 of 11 patients), respectively. In contrast, the control group using the standard system relieved high-level anxiety by only 42.9% (three out of seven patients). Conclusion: The patient-friendly AV system may reduce anxiety in patients undergoing MRI examinations. Implications for practice: The patient-friendly AV system may reduce anxiety in patients undergoing MRI examination by providing a more patient-centered MRI examination environment. These findings may help ameliorate negative perceptions associated with MRI examination.